Weak-acid-resistant calcium carbonate as well as preparation method and application thereof
The weakly resistant calcium carbonate is prepared by dry method, and the water glass and sodium fluorosilicate are used for modification and curing, and then a composite modifier is added to form a protective layer, which solves the problem of calcium carbonate reacting in an acidic environment and improves acid resistance and product quality.
Patent Information
- Application Number
- CN202411415802.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-25
AI Technical Summary
Calcium carbonate easily reacts to produce bubbles, holes, and powdering in an acidic environment, affecting the quality of downstream products. In addition, the existing wet coating methods have high energy consumption, large amount of modifiers, and easy to agglomerate.
The weakly resistant calcium carbonate is prepared by dry method, and the first modification is performed by mixing the water glass solution with the calcium carbonate powder, and then surface curing is performed using sodium fluorosilicate solution, and then adding a composite modifier for the second modification to form an acid-resistant protective layer.
It improves the acid resistance of calcium carbonate powder, avoids agglomeration, reduces production energy consumption and modifier dosage, and significantly improves the quality and application performance of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fine chemical industry, and in particular to weakly acid-resistant calcium carbonate and a preparation method and application thereof. Background Art
[0002] Calcium carbonate, as a common inorganic compound, is widely present in nature. It is the main component of limestone, calcite, marble, etc. It is also one of the most widely used and cheapest raw materials in industry, commonly known as "industrial MSG". It plays a role in physical filling, performance enhancement, and cost saving in the fields of plastics, coatings, rubber, papermaking, etc.
[0003] The chemical properties of calcium carbonate are alkaline. The pH value of heavy calcium carbonate produced by grinding method is 8-10, and the pH value of light calcium carbonate produced by chemical method is above 10. Calcium carbonate easily reacts with acid to generate CO 2 , generating a large number of bubbles. In some weakly acidic production systems or occasions that may be exposed to weakly acidic environments, such as industrial paint, weakly acidic paper, artificial leather and other industries, calcium carbonate reacts with acid to generate CO 2 Gas can easily cause bubbles, holes, and powdering in products, which can have a serious impact on the quality of downstream products.
[0004] In order to improve the acid resistance of calcium carbonate powder, calcium carbonate powder is often wet coated. Modifiers such as silicates, barium salts, aluminum salts, and metaphosphates are prepared into slurry to coat calcium carbonate with an acid-resistant protective film. However, wet production has high energy consumption, large amounts of modifiers, and requires filter pressing, drying, and crushing in the later stage. The product is also prone to agglomeration during drying and crushing, resulting in a decrease in product performance. In addition, some modifiers have a loose and porous structure, and even if modified, they are easy to allow acidic substances to pass through, causing calcium carbonate to react and generate bubbles. Summary of the invention
[0005] The purpose of the present invention is to provide a weakly acid-resistant calcium carbonate and a preparation method and application thereof, so as to improve the acid resistance of calcium carbonate powder and solve the problem that the product is easy to agglomerate in the later stage.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A method for preparing weakly acid-resistant calcium carbonate comprises the following steps:
[0008] 1) mixing a water glass solution with a calcium carbonate powder, and performing a first modification to obtain a modified calcium carbonate powder;
[0009] 2) mixing the sodium fluorosilicate solution with the modified calcium carbonate powder obtained in step 1) and performing surface curing to obtain cured calcium carbonate powder;
[0010] 3) mixing the solidified calcium carbonate powder with a composite modifier and performing a second modification to obtain the weakly acid-resistant calcium carbonate;
[0011] Step 3) The composite modifier comprises coconut oil, 3 # At least one of white oil and DOP.
[0012] Optionally, in step 1), the mass ratio of water glass to solvent in the water glass solution is 2-3:1-2; the mass ratio of the water glass solution to the calcium carbonate powder is 3-7:100.
[0013] Optionally, the solvent in the water glass solution is water, and the modulus of the water glass is 2.6 to 2.8.
[0014] The preparation method according to claim 1 is characterized in that the temperature of the first modification is 20 to 30°C, the time is 15 to 30 min, and the stirring rate is 800 to 1600 r / min.
[0015] Optionally, the solvent in the sodium fluorosilicate solution in step 2) is water, the mass ratio of sodium fluorosilicate to solvent in the sodium fluorosilicate solution is 0.5-1.5:0.5-1.5, and the mass ratio of the sodium fluorosilicate solution to the calcium carbonate powder in step 1) is 2-4:100.
[0016] Optionally, in step 2), the surface curing temperature is 20-35° C., the time is 10-15 min, and the stirring rate is 800-1600 r / min.
[0017] Optionally, the mass ratio of coconut oil, 3# white oil and DOP in the composite modifier of step 3) is 0-5:0-5:0-2, and the amount of coconut oil, 3# white oil and DOP is not 0 at the same time; the mass ratio of the composite modifier to the calcium carbonate powder of step 1) is 12-25:1000.
[0018] Optionally, in step 3), the temperature of the second modification is 120-140° C., the time is 10-20 min, and the stirring rate is 1200-1600 r / min.
[0019] The invention provides weakly acid-resistant calcium carbonate prepared by the preparation method.
[0020] The invention also provides application of the weakly acid-resistant calcium carbonate in industrial paint, weakly acidic paper or artificial leather.
[0021] The present invention mixes a water glass solution with a calcium carbonate powder, performs a first modification, and obtains a modified calcium carbonate powder. During the modification process, the water glass and sodium fluorosilicate react to generate orthosilicic acid; the sodium fluorosilicate solution is then mixed with the obtained modified calcium carbonate powder for curing. During the curing process, the orthosilicic acid forms an acid-resistant silica gel when heated under anhydrous conditions, and pores are easily formed in the gel layer; a composite modifier is then added for a second modification, and the composite modifier is wrapped and adsorbed on the surface of the porous gel to form a protective layer that isolates acidic substances, thereby obtaining the weakly acid-resistant calcium carbonate. The weakly acid-resistant calcium carbonate powder obtained by the present invention has improved acid resistance in application, is not prone to agglomeration, and solves the quality impact of bubbles, holes, and pulverization of calcium carbonate on downstream products in an acidic environment through the improvement of acid resistance.
[0022] The present invention adopts a dry method for surface coating, and the present invention solves the problem that acidic substances easily corrode calcium carbonate through pores. After calcium carbonate powder is modified by water glass, sodium fluorosilicate solution is used for surface curing, and then a composite modifier is used for surface coating to fill the gaps, so that the calcium carbonate particles are coated more densely and the dispersibility of the calcium carbonate particles is improved.
[0023] In the process of surface solidification, the present invention utilizes the heat generated by shearing in a high-speed disperser to stir and heat the powder to remove moisture therein.
[0024] The method for preparing acid-resistant calcium carbonate of the present invention not only has low energy consumption, but also has high utilization rate of modified materials. The acid resistance of the prepared acid-resistant calcium carbonate powder is improved, and the quality impact of bubbles, holes and pulverization of calcium carbonate on downstream products in an acidic environment is solved.
[0025] The acid-resistant calcium carbonate prepared by the invention is not prone to agglomeration during application. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing weakly acid-resistant calcium carbonate, comprising the following steps:
[0027] 1) mixing a water glass solution with a calcium carbonate powder, and performing a first modification to obtain a modified calcium carbonate powder;
[0028] 2) mixing the sodium fluorosilicate solution with the modified calcium carbonate powder obtained in step 1) and performing surface curing to obtain cured calcium carbonate powder;
[0029] 3) mixing the solidified calcium carbonate powder with a composite modifier and performing a second modification to obtain the weakly acid-resistant calcium carbonate;
[0030] Step 3) The composite modifier comprises at least one of coconut oil, 3# white oil and DOP.
[0031] In the present invention, the mass ratio of water glass to solvent in the water glass solution in step 1) is preferably 2-3:1-2, more preferably 2.2-2.8:1.2-1.8, and more preferably 2.5-2.6:1.5-1.6; the mass ratio of the water glass solution to the calcium carbonate powder is preferably 3-7:100, more preferably 4-6:100, and even more preferably 5-5.5:100.
[0032] In the present invention, the solvent in the water glass solution is preferably water, and the modulus of the water glass is preferably 2.6 to 2.8, and more preferably 2.6 to 2.7.
[0033] In the present invention, the preparation method of the calcium carbonate powder is preferably that the calcite raw material is washed and then crushed by a jaw crusher and a rotary cone crusher in sequence, the crushed material is sieved by a linear vibrating screen, the particle size of the calcite particles is controlled to be ≤2mm, the material is stored in a large storage tank for homogenization storage, and then ground by a ceramic lined ball mill; in the present invention, the purpose of the grinding is to meet downstream demand, and the grinding fineness can be adjusted according to actual needs, and the grinding fineness is preferably 600-2500 mesh, and more preferably 800-2000 mesh.
[0034] The present invention preferably adopts a ceramic-lined ball mill for grinding, which does not generate iron filings during grinding and can effectively avoid the introduction of unstable impurities.
[0035] In the present invention, the temperature of the first modification is preferably 20-30°C, more preferably 22-28°C, more preferably 25-26°C; the time is preferably 15-30 min, more preferably 20-25 min; the stirring rate is preferably 800-1600 r / min, more preferably 1200-1500 r / min.
[0036] In the present invention, the sodium fluorosilicate solution in step 2) is preferably mixed with the modified calcium carbonate powder obtained in step 1) by spraying the sodium fluorosilicate solution into the modified calcium carbonate powder obtained in step 1).
[0037] In the present invention, the solvent in the sodium fluorosilicate solution in step 2) is preferably water, the mass ratio of sodium fluorosilicate to solvent in the sodium fluorosilicate solution is preferably 0.5-1.5:0.5-1.5, more preferably 0.7-1.3:0.7-1.3, more preferably 1:1, and the mass ratio of the sodium fluorosilicate solution to the calcium carbonate powder in step 1) is preferably 2-4:100, more preferably 2-3:100.
[0038] In the present invention, the temperature of the surface curing in step 2) is preferably 20-35°C, more preferably 25-30°C, the time is preferably 10-15min, more preferably 11-14min, more preferably 12-13min; the stirring rate is preferably 800-1600r / min, more preferably 1000-1500r / min, and further preferably 1200-1400r / min.
[0039] In the present invention, after the surface curing is completed, the equipment is preferably heated to the second modified temperature and stirred for 15 minutes, and the heat generated by shearing in the high-speed disperser is used to stir and heat the powder to remove moisture therein; the stirring rate of this process is not particularly limited.
[0040] In the present invention, the coconut oil, 3 # The mass ratio of white oil to DOP is preferably 0-5:0-5:0-2, and the amount of coconut oil, 3# white oil and DOP is not 0 at the same time; more preferably 3 # The mass ratio of white oil and DOP is 1:1 or coconut oil and 3 # The mass ratio of white oil is 3:2 or the mass ratio of coconut oil and DOP is 5:1.
[0041] In the present invention, the mass ratio of the composite modifier to the calcium carbonate powder in step 1) is preferably 12 to 25:1000, more preferably 15 to 22:1000, and even more preferably 18 to 20:1000.
[0042] In the present invention, in step 3), the temperature of the second modification is preferably 120-140°C, more preferably 125-135°C, and more preferably 130°C; the time is preferably 10-20 min, more preferably 12-18 min, and more preferably 15-16 min; the stirring rate is preferably 1200-1600 r / min, and more preferably 1400-1500 r / min.
[0043] In the present invention, steps 1) to 3) are preferably carried out in a high-speed disperser, respectively.
[0044] The invention provides weakly acid-resistant calcium carbonate prepared by the preparation method.
[0045] The invention also provides application of the weakly acid-resistant calcium carbonate in industrial paint, weakly acidic paper or artificial leather.
[0046] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0047] Example 1
[0048] High-quality calcite raw materials are selected, and after cleaning, they are successively fed into jaw crushers and rotary cone crushers for crushing. The crushed materials are sieved using a linear vibrating screen to control the particle size of the crushed calcite particles to be ≤2mm. The materials are stored in large storage tanks for homogenization and then ground into 800 mesh using a ceramic-lined ball mill to obtain calcium carbonate powder.
[0049] The calcium carbonate powder is added to a high-speed disperser, and a water glass solution prepared by mixing water glass with a modulus of 2.6 and water in a mass ratio of 2:1 is sprayed in for surface modification. The mass of the water glass solution used is 3% of the mass of the calcium carbonate powder. The powder is dispersed at a high speed of 1600 r / min at 25°C for 20 minutes. After the modification is completed, the powder is collected in a storage tank and cooled to room temperature to obtain the modified calcium carbonate powder.
[0050] The modified calcium carbonate powder is added into a high-speed disperser, and a sodium fluorosilicate solution is sprayed into the disperser for surface curing treatment; wherein the sodium fluorosilicate solution is prepared by mixing fluorosilicic acid and water in a mass ratio of 1:1, and the mass of the sodium fluorosilicate solution used is 2% of the mass of the calcium carbonate powder, and the powder is dispersed at a high speed of 1600 r / min for 10 minutes at a stirring rate of 25°C;
[0051] After the curing treatment, the equipment was heated to 140℃ and stirred for 15 minutes, and then the composite modifier was added for the second coating. The composite modifier was 3 # White oil and DOP, 3 # The mass ratio of white oil to DOP is 3:1, the amount of the composite modifier is 12‰ of the mass of the calcium carbonate powder, stirring is carried out at 140°C for 15 minutes at a stirring rate of 1200 r / min, and the weakly acid-resistant calcium carbonate powder is obtained by passing through a 325-mesh sieve.
[0052] Example 2
[0053] The calcium carbonate powder prepared in Example 1 is added to a high-speed disperser, and a water glass solution prepared by mixing water glass with a modulus of 2.7 and water in a mass ratio of 2:1 is sprayed in for surface modification, wherein the mass of the water glass solution used is 5% of the mass of the calcium carbonate powder, and the mixture is dispersed at a high speed of 1600 r / min for 25 minutes at a temperature of 25° C. After the modification is completed, the mixture is collected in a storage tank and cooled to room temperature to obtain the modified calcium carbonate powder;
[0054] The modified calcium carbonate powder is added into a high-speed disperser, and a sodium fluorosilicate solution is sprayed into the disperser for surface curing treatment; wherein the sodium fluorosilicate solution is prepared by mixing fluorosilicic acid and water in a mass ratio of 1:1, and the mass of the sodium fluorosilicate solution used is 3% of the mass of the calcium carbonate powder, and the powder is dispersed at a high speed of 1500 r / min for 10 minutes at a stirring rate of 1500 r / min at 30°C;
[0055] After the curing treatment, the equipment was heated to 140℃ and stirred for 15 minutes, and then the composite modifier was added for the second coating, wherein the composite modifier was coconut oil and 3 # White oil, coconut oil and 3 # The mass ratio of white oil is 3:2, the amount of composite modifier used is 15‰ of the mass of calcium carbonate powder, stirring time is 15min at 140°C at a stirring rate of 1500r / min, and the weakly acid-resistant calcium carbonate powder is obtained by passing through a 325-mesh sieve.
[0056] Example 3
[0057] The calcium carbonate powder prepared in Example 1 is added to a high-speed disperser, and a water glass solution prepared by mixing water glass with a modulus of 2.7 and water in a mass ratio of 2:1 is sprayed in for surface modification, wherein the mass of the water glass solution used is 7% of the mass of the calcium carbonate powder, and the mixture is dispersed at a high speed of 1200 r / min for 30 min at 25° C. After the modification is completed, the mixture is collected in a storage tank and cooled to room temperature to obtain the modified calcium carbonate powder;
[0058] The modified calcium carbonate powder is added into a high-speed disperser, and a sodium fluorosilicate solution is sprayed into the disperser for surface curing treatment, wherein the sodium fluorosilicate solution is prepared by mixing fluorosilicic acid and water in a mass ratio of 1:1, and the mass of the sodium fluorosilicate solution used is 4% of the mass of the calcium carbonate powder, and the mixture is dispersed at a high speed of 1400 r / min for 10 minutes at a stirring rate of 30°C;
[0059] After the curing treatment, the equipment was heated to 140°C and continued to stir for 15 minutes, and then a composite modifier was added for a second coating, wherein the composite modifier was coconut oil and DOP, the mass ratio of coconut oil to DOP was 5:1, the amount of the composite modifier was 20‰ of the mass of the calcium carbonate powder, and the stirring time was 15 minutes at 140°C at a stirring rate of 1400 r / min, and the weakly acid-resistant calcium carbonate powder was obtained through a 325-mesh sieve.
[0060] Comparative Example 1
[0061] High-quality calcite raw materials are selected, and after cleaning, they are successively fed into jaw crushers and rotary cone crushers for crushing. The crushed materials are sieved using a linear vibrating screen to control the particle size of the crushed calcite particles to be ≤2mm. The materials are stored in large storage tanks for homogenization and then ground into 800 mesh using a ceramic-lined ball mill to obtain calcium carbonate powder.
[0062] Performance comparison
[0063] (i) The weakly acid-resistant calcium carbonate powders obtained in Examples 1 to 3 were respectively prepared with water in a mass ratio of 1:1 to form solutions, and the calcium carbonate powder obtained in Comparative Example 1 was prepared with water in a mass ratio of 1:1 to form solutions. The four solutions were adjusted to an acidic environment using dilute hydrochloric acid and placed for 24 hours. The changes in pH of different solutions before and after 24 hours are shown in Table 1.
[0064] Table 1 Changes in pH of different solutions before and after 24 hours
[0065] sample pH before 24h pH after 24h Example 1 5.13 5.94 Example 2 5.72 6.39 Example 3 5.56 6.31 Comparative Example 1 5.34 7.85
[0066] It can be found from Table 1 that the pH of the weakly acid-resistant calcium carbonates prepared in Examples 1 to 3 of the present invention changed little after being placed for 24 hours, and the solution was still in an acidic environment, indicating that the products all had a certain acid resistance. However, the pH of the calcium carbonate powder obtained in Comparative Example 1 changed greatly after being placed for 24 hours, showing alkalinity, indicating that the acid in the solution was completely consumed, indicating that ordinary calcium carbonate had poor acid resistance. This may be because calcium carbonate is alkaline and will react with acid in solution. When calcium carbonate is excessive, the solution is finally alkaline after the reaction ends. When the surface of the calcium carbonate particles is coated with acid-resistant substances, calcium carbonate is difficult to react with the acid in the solution and cannot consume the acid in the solution. The final solution is still acidic.
[0067] (ii) The weakly acid-resistant calcium carbonate powder obtained in Example 1, the calcium carbonate powder obtained in Comparative Example 1, and the commercially available calcium carbonate powder of the same type with a mesh size of 800 (active heavy calcium carbonate produced by Chengjiang Mining) were respectively prepared into slurries (the slurry formula was: 10 wt% styrene-acrylic emulsion, 40 wt% powder, and 50 wt% water. After mixing the components, the slurry was stirred at 600 r / min for 2 min to obtain the corresponding slurry). The scraper fineness was tested. Specifically, several drops of slurry were dripped into the deep part of the groove of the scraper fineness meter to fill the groove and slightly It is better to have excess. Hold the scraper with both hands and place it horizontally on the upper end of the scraper fineness meter, so that the scraper is perpendicular to the surface of the scraper fineness meter, and pull the scraper from the deep part of the groove to the shallow part at a suitable speed, so that the slurry fills the groove and there is no excessive slurry left on the plate; after scraping and pulling, immediately (no more than 5 seconds) pinch the fineness meter horizontally and tilt it, so that the line of sight is at an angle of 15 to 30 degrees to the groove plane and observe the scale value where the particles in the groove are evenly exposed. The reading value is the fineness of the measured sample; finally, the scraper fineness test results of different slurries are obtained, as shown in Table 2:
[0068] Table 2 Scraper fineness test results of different slurries
[0069] sample Scraper fineness Comparative Example 1 48μm Commercially available 65μm Example 1 53μm
[0070] The larger the scraper fineness, the coarser the powder particles. It can be found from Table 2 that the weakly acid-resistant calcium carbonate powder prepared in Example 1 has a small effect on the particle size while improving the acid resistance, while the commercially available similar products have a greater effect on the particle size.
[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing weakly acid-resistant calcium carbonate, characterized in that: The following steps are involved: 1) mixing a water glass solution with a calcium carbonate powder, and performing a first modification to obtain a modified calcium carbonate powder; 2) mixing the sodium fluorosilicate solution with the modified calcium carbonate powder obtained in step 1) and performing surface curing to obtain cured calcium carbonate powder; 3) mixing the solidified calcium carbonate powder with a composite modifier and performing a second modification to obtain the weakly acid-resistant calcium carbonate; Step 3) The composite modifier comprises coconut oil, 3 # At least one of white oil and DOP.
2. The preparation method according to claim 1, characterized in that: Step 1) The mass ratio of water glass to solvent in the water glass solution is 2-3:1-2; the mass ratio of the water glass solution to the calcium carbonate powder is 3-7:
100.
3. The preparation method according to claim 2, characterized in that: The solvent in the water glass solution is water, and the modulus of the water glass is 2.6-2.
8.
4. The preparation method according to claim 1, characterized in that: The temperature of the first modification is 20-30° C., the time is 15-30 min, and the stirring rate is 800-1600 r / min.
5. The preparation method according to claim 1, characterized in that: The solvent in the sodium fluorosilicate solution of step 2) is water, the mass ratio of sodium fluorosilicate to solvent in the sodium fluorosilicate solution is 0.5-1.5:0.5-1.5, and the mass ratio of the sodium fluorosilicate solution to the calcium carbonate powder of step 1) is 2-4:
100.
6. The preparation method according to claim 1 or 5, characterized in that: Step 2) The surface curing temperature is 20-35°C, the time is 10-15 minutes, and the stirring rate is 800-1600 r / min.
7. The preparation method according to claim 1, characterized in that: Step 3) Coconut oil, 3 # The mass ratio of white oil and DOP is 0-5:0-5:0-2 and coconut oil, 3 # The amounts of white oil and DOP are not the same and are 0; the mass ratio of the composite modifier to the calcium carbonate powder in step 1) is 12-25:1000.
8. The preparation method according to claim 1 or 7, characterized in that: Step 3) The temperature of the second modification is 120-140°C, the time is 10-20 min, and the stirring rate is 1200-1600 r / min.
9. Weakly acid-resistant calcium carbonate obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the weakly acid-resistant calcium carbonate according to claim 9 in industrial paint, weakly acidic paper or artificial leather.